Building characteristics and energy use of energy-efficient renovated offices - Kwon, Minyoung (A+BE | Architecture and the Built Environment, 2020)
Chapter 2 presented the physical and psychological satisfaction parameters for user-focused evaluation. In most renovation projects, the façade is a major consideration next to the HVAC system to optimise the performance of the building. Many studies reveal that façade renovation has a large impact on the energy efficiency. The aim of this chapter is to identify the characteristics of renovated offices, such as façade types, HVAC system, and sun shading, and compare the energy performance based on user typologies in renovated and non-renovated office buildings. Section 3.2 describes an overview of façade renovation strategies based on literature. The renovation strategies are classified into four strategies: passive add-in, replacement, climate skin, and active add-in. Section 3.3 presents the criteria to select case studies. Section 3.4 describes the characteristics of four renovated case studies and one non-renovated case located in the Netherlands. The building information was collected through interviews with architects, a review of project documents, and a field survey. Cross-analysis was used to compare the renovation plan, physical conditions. Energy consumption of each office building was compared by different energy metrics in section 3.5. Section 3.6 discusses the limitation of the renovation projects and suggestions for the future study. The finding from cross-evaluation of case studies are described in section 3.7.